CP-024 Factors affecting uptake of biosimilars. (25th February 2017) - Aladul, M; Fitzpatrick, R; Chapman, S
Abstract : Background: 10 years ago the term biosimilar was first used to describe a similar copy of biological drugs in Europe. Since then, 19 biosimilars have been approved by the European Medicine Agency, but uptake has varied across Europe. Purpose: To compare the utilisation of human growth hormone (HGH), erythropoietin (EPO) and granulocyte–colony stimulating factor (G-CSF) biosimilars, and identify whether it is cost or other potential factors which influence their uptake. Material and methods: Secondary care prescribing data between 2007 and 2015 for HGH, EPO and G-CSF were extracted from the IMS Health database and analysed using linear regression. Correlation analysis was performed between utilisation and price. Results: Utilisation of G-CSF biosimilars increased by 12.16% (95% CI 7.81–16.51) per year on average (p>0.000), and achieved 84% of the G-CSF market by 2015. A moderate to strong correlation existed between G-CSF utilisation and price of biosimilars. In stark contrast, utilisation for HGH biosimilars increased slightly by 0.9% (95% CI 0.63–1.16) per year on average (p>0.000) and EPO biosimilars by only 0.45% (95% CI 0.079–0.85) per year on average (p>0.025). HGH and EPO biosimilars achieved only 6% and 3% of the HGH and EPO markets, respectively, by 2015. A weak or no correlation existed between utilisation and price of HGH and EPO biosimilars. Conclusion: Uptake of G-CSF biosimilars was driven by unit cost while other factors appear to have influenced the uptake of HGH and EPO. The key differences were the advances in formulations and devices available for HGH and EPO, which increased ease of administration and potentially prescriber and patient preferences. There were also potential safety concerns with switching formulations of EPO. Therefore, cost only influences uptake in the absence of safety concerns or prescriber or patient preferences for new formulations or devices. References and/or acknowledgements: We are grateful to IMS Health for the supply of the data. No conflict of interest